# Eq2 2

Solve following equation with quadratic members and rational function:

(x2+1)/(x-4) + (x2-1)/(x+3) = 23

Result

x1 =  -2.733
x2 =  5.786
x3 =  8.947

#### Solution:

Leave us a comment of example and its solution (i.e. if it is still somewhat unclear...):

Showing 1 comment:

#### To solve this verbal math problem are needed these knowledge from mathematics:

Looking for help with calculating roots of a quadratic equation? Do you have a linear equation or system of equations and looking for its solution? Or do you have quadratic equation?

## Next similar examples:

1. Reciprocal equation 2
Solve this equation: x + 5/x - 6 = 4/11
2. Solve 3
Solve quadratic equation: (6n+1) (4n-1) = 3n2
3. Variation equation
Solve combinatorics equation: V(2, x+8)=72
Which of the points belong function f:y= 2x2- 3x + 1 : A(-2, 15) B (3,10) C (1,4)
5. Equation
Eequation f(x) = 0 has roots x1 = 64, x2 = 100, x3 = 25, x4 = 49. How many roots have equation f(x2) = 0 ?
6. Variable
Find variable P: PP plus P x P plus P = 160
7. Discriminant
Determine the discriminant of the equation: ?
8. Equation
Equation ? has one root x1 = 8. Determine the coefficient b and the second root x2.
9. Roots
Determine the quadratic equation absolute coefficient q, that the equation has a real double root and the root x calculate: ?
Find the roots of the quadratic equation: 3x2-4x + (-4) = 0.